Methylenetetrahydrofolate reductase gene polymorphism and its association with coronary artery disease - Guerzoni, Alexandre Rodrigues (2007)
CONTEXT AND OBJECTIVE: Obstructive coronary artery disease (CAD) is characterized by the deposition of atherosclerotic plaque on the coronary artery wall. Its manifestations depend on interactions between environmental and genetic risk factors. The aim of this work was to analyze the frequency of methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism in patients with CAD and its association with plasma homocysteine levels. Risk factors for CAD were also evaluated. DESIGN AND SETTING: Retrospective with blind quantitative analysis, at Hospital de Base, Faculdade de Medicina de São José do Rio Preto. METHODS: One hundred and twenty-seven individuals were studied. All completed a questionnaire to analyze risk factors for CAD. MTHFR polymorphism was investigated by restriction fragment length analysis and correlated with the number of affected arteries and degree of arterial obstruction determined by coronary cineangiography, and with plasma homocysteine levels measured by liquid chromatography/sequential mass spectrometry. RESULTS: Smoking (p = 0.02) and high-density lipoprotein cholesterol (p = 0.01) were associated with CAD. The C allele was the most prevalent in patients (0.61) and controls (0.66). There was no correlation between MTHFR/C677T polymorphism and plasma homocysteine levels. However, in patients with the TT genotype there was a correlation with the prevalence of coronary obstruction greater than 95% (p = 0.02) and the presence of two affected arteries (p = 0.04). CONCLUSIONS: The TT genotype is associated with coronary artery obstruction greater than 95% and the presence of two affected arteries. This confi rms the relationship between genetic variants in specific patient subgroups and cardiovascular diseases.